2017
DOI: 10.1089/end.2017.0427
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Cost Analysis of a Single-Center Reusable Flexible Ureterorenoscopy Program: A Comparative Cost Simulation of Disposable fURS as an Alternative

Abstract: Disposable fURS is a more expensive option for high-volume centers. Based on our case analysis, laser disintegration treatment of multiple, large stones in the lower kidney pole of recurrent stone formers, as well as a steep infundibulopelvic angle (IPA ≤50°), seems to be the main risk factor for fURS damage. For these cases, disposable fURS may be a cost-effective alternative; however, a prospective comparison of economic outcomes between disposable and reusable fURS, together with confirmation of the propose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 18 publications
0
45
0
2
Order By: Relevance
“…Of the remaining 646 studies, 59 published between 2000 and 2018 were considered of relevance to the pre-defined queries and were selected for further analysis. The studies consisted of four randomized controlled trial 9,11,38,56 , three multicenter trials 17,30,33 , 40 case series 5,8,10,12,13,15,16,[25][26][27][28][29]31,32,[34][35][36][37]39,41,42,[44][45][46][47][48][49][50][51][52]54,55,[57][58][59][60][61][62][63]66 , one cadaveric feasibility study 18 , one animal feasibility study 19 , and ten bench top studies…”
Section: Resultsmentioning
confidence: 99%
“…Of the remaining 646 studies, 59 published between 2000 and 2018 were considered of relevance to the pre-defined queries and were selected for further analysis. The studies consisted of four randomized controlled trial 9,11,38,56 , three multicenter trials 17,30,33 , 40 case series 5,8,10,12,13,15,16,[25][26][27][28][29]31,32,[34][35][36][37]39,41,42,[44][45][46][47][48][49][50][51][52]54,55,[57][58][59][60][61][62][63]66 , one cadaveric feasibility study 18 , one animal feasibility study 19 , and ten bench top studies…”
Section: Resultsmentioning
confidence: 99%
“…The detailed course of fURS procedures performed at our department has already been described in previous articles from our working group [7,8]. In summary, written patient consent was obtained at least 24 h preoperatively.…”
Section: Methodsmentioning
confidence: 99%
“…Due to its minimal invasiveness and acceptable level of difficulty, fURS has already been incorporated into many departments as a part of residents' training. On the other Urol Int 2020;104:452-458 DOI: 10.1159/000504989 hand, a persistent time pressure in the operation theatre, a substantial intra-and postoperative complication rate [5,6], as well as economic and logistic consequences of reusable flexible ureteroscope damage [7] challenge training aims, operative efficiency, and patient safety. The goal of our study was to retrospectively analyze the influence of residents' participation in fURS procedures on intraand postoperative outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Concerns over the sterilizing process for reusable fURS and their link to the transmission of infection between patients, and an increasing consciousness about the environmental impact of fURS have also elevated the profile of single‐use fURS . Several studies have shown that single‐use fURS are becoming more economically viable, especially in lower‐volume centers and for cases with a higher risk of damage to reusable fURS . Several studies have shown that reusable fURS suffer damage requiring repair after 10–25 cases .…”
Section: Introductionmentioning
confidence: 99%
“…5 Several studies have shown that single-use fURS are becoming more economically viable, especially in lower-volume centers and for cases with a higher risk of damage to reusable fURS. [6][7][8] Several studies have shown that reusable fURS suffer damage requiring repair after 10-25 cases. 9,10 Once a ureteroscope has been repaired, it is more likely to be damaged again, requiring further repair.…”
Section: Introductionmentioning
confidence: 99%